Discovery of oxa-sultams as RORc inverse agonists showing reduced lipophilicity, improved selectivity and favorable ADME properties. Issue 18 (15th September 2016) - René, Olivier; Fauber, Benjamin P.; Barnard, Adrian; Chapman, Kerry; Deng, Yuzhong; Eidenschenk, Céline; Everett, Christine; Gobbi, Alberto; Johnson, Adam R.; La, Hank; Norman, Maxine; Salmon, Gary; et al.
Graphical abstract: Abstract: Modification of the δ-sultam ring of RORc inverse agonist2 led to the discovery of more polar oxa -sultam65 . The less lipophilic inverse agonist (65 ) displayed high potency in a biochemical assay, which translated into inhibition of IL-17 production in human peripheral blood mononuclear cells. The successful reduction of lipophilicity of this new analog gave rise to additional improvements in ROR selectivity and aqueous kinetic solubility, as well as reduction in plasma protein binding, while maintaining high cellular permeability.